Evaluation of various diagnostic techniques in donkeys experimentally infected with Trypanosoma evansi* - BHATNAGAR, C S; L PATHAK, K M; KAPOOR, M; YADAV, M P (The Indian Journal of Animal Sciences, 2013)
Evaluation of various diagnostic tests, viz. parasitological tests (wet blood film -WBF), biological test (mouse subinoculation - MSI) and immunodiagnostic tests based on antibody detection (double immunodiffusion test - DID), antigen detection (double antibody sandwich enzyme linked immunosorbent assay Ag-ELlSA) was done in donkeys experimentally infected with Trypanosoma evansi. WBF and MSI detected the infection as early as 96 hr and 48 hr post - infection respectively. Antibodies were detected as early as 13 days post -infection, while the trypanosomal antigens were detected as early as 7 days post - infection. The diagnostic efficacy of MSI was 100% followed by Ag- ELISA, WBF and DID.